2015
DOI: 10.5539/jsd.v8n3p124
|View full text |Cite
|
Sign up to set email alerts
|

Rural Tourism Destination Performance in East Malaysia: Influencing Factors from the Communities’ Perspective

Abstract: Rural tourism is a rapidly growing tourism segment and has been given increasing importance, in view of its potential to contribute economic growth to the rural areas. However, any rural tourism destination development should be implemented in a way that maximises destination performance. In our study, we examine the relationship between support and participation of the local government, community leadership in tourism, community attitudes towards tourism, and community support towards tourism with destination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
4
1
Order By: Relevance
“…The impact of community participation was small, which was one of the differences between urban and rural tourism communities. Previous studies in rural community tourism have shown that residents' attitudes and community leadership had a significant positive impact, while government's support had little impact [37]. However, our results showed that residents' willingness to participate and government's policy support were slightly less important than community managers' willingness to support.…”
Section: Conclusion and Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…The impact of community participation was small, which was one of the differences between urban and rural tourism communities. Previous studies in rural community tourism have shown that residents' attitudes and community leadership had a significant positive impact, while government's support had little impact [37]. However, our results showed that residents' willingness to participate and government's policy support were slightly less important than community managers' willingness to support.…”
Section: Conclusion and Discussioncontrasting
confidence: 69%
“…Residents' willingness to participate Cheuk et al [37] Community managers' willingness to support Government's policy support Table 2. Explanation of indicators.…”
Section: Community Participationmentioning
confidence: 99%
“…The aborigine group more easily searched for information on the landscape in the square space and street space than the tourists, which is because these two types of spaces are their daily life spaces and they are familiar with their landscapes [90]. The landscape elements in the street space, such as the gables of the buildings and changing landscape walls, were more likely to attract the subject's attention.…”
Section: Analysis Of Differences In Landscape Preferences Of Differen...mentioning
confidence: 99%
“…Community leadership has been studied in a range of subject areas, for examples in education (e.g. Bukoski et al, 2015;Riley, 2012), health (Trapence et al, 2012), local government (Sullivan, 2007), local politics (Bénit-Gbaffou and Katsaura, 2014) and tourism (Cheuk et al, 2015).…”
Section: Community Leadershipmentioning
confidence: 99%